Intestinal stem cells and gut microbiota therapeutics: hype or hope? - Ahmad Sophien, Ahmad Naqiuddin; Jusop, Amirah Syamimi; Tye, Gee Jun; Tan, Yuen-Fen; Wan Kamarul Zaman, Wan Safwani; Nordin, Fazlina (Frontiers in Medicine, 2023)
The vital role of the intestines as the main site for the digestion and absorption of nutrients for the body continues subconsciously throughout one’s lifetime, but underneath all the complex processes lie the intestinal stem cells and the gut microbiota that work together to maintain the intestinal epithelium. Intestinal stem cells (ISC) are multipotent stem cells from which all intestinal epithelial cells originate, and the gut microbiota refers to the abundant collection of various microorganisms that reside in the gastrointestinal tract. Both reside in the intestines and have many mechanisms and pathways in place with the ultimate goal of co-managing human gastrointestinal tract homeostasis. Based on the abundance of research that is focused on either of these two topics, this suggests that there are many methods by which both players affect one another. Therefore, this review aims to address the relationship between ISC and the gut microbiota in the context of regenerative medicine. Understanding the principles behind both aspects is therefore essential in further studies in the field of regenerative medicine by making use of the underlying designed mechanisms.